British Association of Dermatologists guidelines for the management of adults with basal cell carcinoma 2021. (1st November 2021) - Nasr, I.; McGrath, E.J.; Harwood, C.A.; Botting, J.; Buckley, P.; Budny, P.G.; Fairbrother, P.; Fife, K.; Gupta, G.; Hashme, M.; Hoey, S.; Lear, J.T.; et al.
Abstract: Linked Comment: M.D. Moncrieff and J.P. Nobes. Br J Dermatol 2021; 185 :877 . Plain language summary available online